Means, Motive, and Opportunity: Do Non-Islet-Reactive Infiltrating T Cells Contribute to Autoimmunity in Type 1 Diabetes? - Rodriguez-Calvo, Teresa; Christoffersson, Gustaf; Bender, Christine; von Herrath, Matthias G.; Mallone, Roberto; Kent, Sally C.; James, Eddie A. (Frontiers in immunology, 2021)
In human type 1 diabetes and animal models of the disease, a diverse assortment of immune cells infiltrates the pancreatic islets. CD8 + T cells are well represented within infiltrates and HLA multimer staining of pancreas sections provides clear evidence that islet epitope reactive T cells are present within autoimmune lesions. These bona fide effectors have been a key research focus because these cells represent an intellectually attractive culprit for β cell destruction. However, T cell receptors are highly diverse in human insulitis. This suggests correspondingly broad antigen specificity, which includes a majority of T cells for which there is no evidence of islet-specific reactivity. The presence of “non-cognate” T cells in insulitis raises suspicion that their role could be beyond that of an innocent bystander. In this perspective, we consider the potential pathogenic contribution of non-islet-reactive T cells. Our intellectual framework will be that of a criminal investigation. Having arraigned islet-specific CD8 + T cells for the murder of pancreatic β cells, we then turn our attention to the non-target immune cells present in human insulitis and consider the possible regulatory, benign, or effector roles that they may play in disease. Considering available evidence, we overview the case that can be made that non-islet-reactive infiltrating T cells should be suspected as co-conspirators or accessories to the crime and suggest some possible routes forward for reaching a better understanding of their role in disease.